A Complicated Relationship: Right-Wing Populism, Media Representation and Journalism Theory (Global Media Journal - German Edition, 2017)
The current upswing of right-wing populism in the United States and in Europe is a challenge not only for policy makers, but also for journalism theory. If and how to report on right-wing politicians, movements and issues is a delicate question that various strands of theory answer differently. Functionalist systems theory is in favor of large-scale coverage due to the stimulating news values of populist debates, although the precise character of the political integration remains unclear. In contrast, rational democratic deliberation theory is to be interpreted as a complete rebuttal of the irrational character of populism. The argument here would be that we must not allow the media be dominated by irrational debates. At the same time, democratic media theory is all but uniform in dealing with the phenomenon. While traditional rational public sphere theory is clearly anti-populist, paradoxically left-liberal and postmodern public sphere theory, anti-elitist and radically post-modern as it is, can be used as an argument for better representation of marginalized voices, including right-wing populists.
Keywords: populism; journalism; democracy; public sphere theory; system theory